Polyfunctionalised nanoparticles bearing robust gadolinium surface units for high relaxivity performance in MRI - Chabloz,N; Wenzel,M; Perry,H; Yoon,I; Molisso,S; Stasiuk,G; Elson,D; Cass,A; Wilton-Ely,J (Chemistry - A European Journal, 2019)
The first example of an octadentate gadolinium unit based on DO3A (hydration number q = 1) with a dithiocarbamate tether has been designed and attached to the surface of gold nanoparticles (around 4.4 nm in diameter). In addition to the superior robustness of this attachment, the restricted rotation of the Gd complex on the nanoparticle surface leads to a dramatic increase in relaxivity (r1) from 4.0 mM1 s1 in unbound form to 34.3 mM1 s1 (at 10 MHz, 37 °C) and 22 ± 2 mM1s1 (at 63.87 MHz, 25 °C) when immobilised on the surface. The ‘onepot’ synthetic route provides a straightforward and versatile way of preparing a range of multifunctional gold nanoparticles. The incorporation of additional surface units improving biocompatibility (PEG and thioglucose units) and targeting (folic acid) lead to little detrimental effect on the high relaxivity observed for these nontoxic multifunctional materials. In addition to the passive targeting attributed to gold nanoparticles, the inclusion of a unit capable of targeting the folate receptors overexpressed by cancer cells, such as HeLa cells, illustrates the potential of these assemblies.